Governance traps in climate change politics: re‐framing the debate in terms of responsibilities and rights. (21st September 2015) - Newell, Peter; Bulkeley, Harriet; Turner, Karen; Shaw, Christopher; Caney, Simon; Shove, Elizabeth; Pidgeon, Nicholas
<x xml:space="preserve">Abstract</x> There is a strong sense of malaise surrounding climate politics today. This has been created at least in part by factors such as the chasm between the scale of action required and the adequacy of current political commitments, stalemate in global negotiations, the low price of carbon, and a growing sense of indifference among the publics of some developed countries about the threat posed by climate change. Within the policy community these issues are generally treated as different problems each to be overcome on their own terms. Yet, we argue, suggested solutions to these problems hold much in common—namely a focus on identifying agency, whether the capacity of institutions to act or the behavior of individuals. What is often missing from such accounts of climate politics is a recognition that the problems of how agency is attributed, what we might term governance traps, are structural in nature. Governing climate change therefore requires that we study the conditions through which these challenges arise and which in turn serve to frame agency in particular ways. We suggest that examining the ways in which notions of responsibilities and rights are currently being framed within climate politics provides one way into these dynamics. This opens up the critical questions that need to be addressed ahead of the critical Conference of the Parties meeting in Paris in November 2015. WIREs Clim Change 2015, 6:535–540. doi: 10.1002/wcc.356 For further resources related to this article, please visit the WIREs website.